A single strand: A simplified approach to DNA origami - Yang, Micah; Bakker, David; Raghu, Dyuti; Li, Isaac T. S. (Frontiers in Chemistry, 2023)
Just as a single polypeptide strand can self-fold into a complex 3D structure, a single strand of DNA can self-fold into DNA origami. Most DNA origami structures (i.e., the scaffold-staple and DNA tiling systems) utilize hundreds of short single-stranded DNA. As such, these structures come with challenges inherent to intermolecular construction. Many assembly challenges involving intermolecular interactions can be resolved if the origami structure is constructed from one DNA strand, where folding is not concentration dependent, the folded structure is more resistant to nuclease degradation, and the synthesis can be achieved at an industrial scale at a thousandth of the cost. This review discusses the design principles and considerations employed in single-stranded DNA origami and its potential benefits and drawbacks.